Vertical barangay designing a holistic public housing complex in the Metro Manila urban setting - Guerrero, Paolo Dominic N. (College of Architecture, University of the Philippines Diliman, 2025)
In light of the current housing backlog in the Philippines, and the ongoing 4PH program which seeks to address this backlog, there is interest in creating and implementing architectural designs for multi-storey mid/high-rise urban housing developments. With this context, the work sought to design a vertical social housing complex in the vicinity of NAIA terminal 1, within the emerging Priority Development Zone of Pasay City. In creating the design, a review of studies and precedents of social housing developments was done; supplemented by data from reports on local housing projects, and responses from interviews with housing stakeholders. From this research and the user and spatial analyses done, three concepts emerged for each level of the design: Space Efficiency at the unit-level, Openness at the building-level, and the Barangay experience at the complex-level. Three unit designs were made (Studio, 1BRLDK, 2BRDK), each intended to suit the needs of families based on their situation. A twin building design emerged from the design process; the design was intended to encourage interaction by opening the space and providing communal spaces on each floor. Lastly, the complex was designed with the intent of supporting a Barangay; amenities commonly found in Barangays (i.e. basketball court, wet market, barangay hall) alongside communal spaces dedicated to assemblies and collaborative activities. The design proposes a socialized housing complex that is able to cater to the needs of the residents, provide spaces that support the community building experience, and enable the formation and longevity of a new Barangay.